1991
DOI: 10.1016/0378-1097(91)90225-y
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the secretory IgA response to Toxoplasma gondii using cholera toxin

Abstract: Our study demonstrates that cholera toxin (CT) markedly enhances the intestinal anti-T. gondii antibody response following oral immunisation of mice with a T. gondii sonicate (TSo) and CT. The antibodies induced were mostly IgA and secretory IgA but a small quantity of IgG was also produced. In contrast, no intestinal anti-T. gondii IgM antibodies were detected. Anti-CT IgA antibodies were also present in intestinal secretions but in much lower quantities than the T. gondii-specific IgA. No anti-CT IgG nor IgM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…It is presently unknown whether adherence mediated by these factors is host-restricted. Indeed, high levels of IgA, an immunoglobulin isotype often invoked as a prime effector of mucosal immunity [42][43][44], were detected in vaginal wash fluids collected from OM-immunized mice. It was reported that the gonococci produced a protease that specifically cleaved human IgA1 into Fab and Fc fragments.…”
Section: Discussionmentioning
confidence: 99%
“…It is presently unknown whether adherence mediated by these factors is host-restricted. Indeed, high levels of IgA, an immunoglobulin isotype often invoked as a prime effector of mucosal immunity [42][43][44], were detected in vaginal wash fluids collected from OM-immunized mice. It was reported that the gonococci produced a protease that specifically cleaved human IgA1 into Fab and Fc fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Representative examples of antigens delivered with CT include tetanus toxoid Xu-Amano et al, 1994;Marinaro et al, 1995), Helicobacter pylori urease (Saldinger et al, 1998;Pappo et al, 1995), pneumococcal polysaccharide or surface proteins (Yamamoto et al, 1997a;Vancott et al, 1996), Haemophilus influenzae lipooligosaccharide (Hong et al, 2010), inactivated influenza virus (Bergmann and Waldman, 1988), Candida albicans (De Bernardis et al, 2002), and Eh29 antigen from Entameba histolytica (Carrero et al, 2010). CT-adjuvanted vaccines potentiate antigen-specific S-IgA, serum IgG, IgM, IgE, and cellular responses (Bourguin et al, 1991;Xu-Amano et al, 1993;Tanaka et al, 2007;Hodge et al, 2001;Nurkkala et al, 2010;Vendetti et al, 2009). The molecular events and immunological actions presumed to induce these responses are described later in this chapter.…”
Section: Cholera Toxinmentioning
confidence: 97%
“…Isotypes and average (ϮSD) levels of antiamebic antibodies were determined as in Fig. 2. amebal antigen, as reported before for several soluble proteins (13,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 85%